2019
DOI: 10.1039/c9ra03382c
|View full text |Cite
|
Sign up to set email alerts
|

Novel N-arylamide derivatives of (S)-perillic acid ((S)-PA): in vitro and in vivo cytotoxicity and antitumor evaluation

Abstract: (S)-Perillic acid derivatives bearing N-aryl moiety with enhanced cytotoxic and antitumor effect against hepatocellular carcinoma and glioblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The research group investigated the in vivo anticancer activity and toxicity against organ or tissue in mice with inoculated hepatoma (H22) cancer cells. The results showed that analogues 24 and 25 exhibit inhibition properties against H22 cells with no major damage to tissues or organs ( Table 1 ) [ 49 ].…”
Section: Perillyl Alcohol and Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The research group investigated the in vivo anticancer activity and toxicity against organ or tissue in mice with inoculated hepatoma (H22) cancer cells. The results showed that analogues 24 and 25 exhibit inhibition properties against H22 cells with no major damage to tissues or organs ( Table 1 ) [ 49 ].…”
Section: Perillyl Alcohol and Its Derivativesmentioning
confidence: 99%
“…In melanoma cells, the propane-1,2-diyl spaced with a terpene moiety of (−)-menthol derivative 48b and (+)-neomenthol derivative 48l displayed growth inhibition at an IC 50 < 4 µM, which is 10-fold lower than seen with cisplatin (Table 1). Furthermore, presented terpene complexes (48,49) were tested for antiproliferative activity in human HT-29 colon cells. Greater and more persistent growth inhibition in HT-29 colon cancer cells upon long-term exposure is induced by the (−)-menthyl ester complexes with 2,3-diaminopropanoate (49a) and 2,4diaminobutanoate (49b) ligands compared with the 6-(aminomethyl)nicotinate analogue 48a.…”
Section: Menthol and Its Derivativesmentioning
confidence: 99%